Políticas públicas no território da cidadania do Vale do Paranã - GO - Ataides, Ludimila Lelis (2017)
The northeast of Goiás is still considered one of the regions of Goiás, with less socioeconomic dynamism. This research understands that geographic location and its characteristics are not the factors that determine the perpetuation of this reality. We understand that the relations of power, between the State and private power, contribute to this recurrence. Thus, based on the analysis of public policy, Citizenship Territory Programs, we investigate how they occur in space. For that, a bibliographical research was carried out, data collection in secondary sources; field research to obtain primary data. Based on theoretical analysis and empirical research, we have identified that power relations influence and are decisive in the effectiveness of public policies aimed at rural development. The absence of the appropriation and understanding of society in relation to public policies are perceived in regions where Colonelism, Clientelism, Patrimonialism, has in its methodology the core of perpetuation of the existing social inequalities, not rupture with the model of landed concentration in the Brazil. In this way, it is important and necessary to rethink how to elaborate and formulate actions that promote the rupture with this mechanism of governing Brazil, in its various scales, beyond the reality found in the North-east of Goiania, specifically in the Territory of the Paranã Valley Citizenship.